Pengembangan Kecerdasan Ekologis Berbasis Experiential Learning Bagi Anak Usia Dini dan Usia Sekolah Dasar Awal - Yurita Erviana Yurii; Roni Muslikah; Lita Lita; Septi Nurhayati; Salis Wahyu Hidayati (Early Stage, 2026)
This research is based on field findings related to the social reality of communities on the verge of anxiety, excessive exploitation of nature, and low awareness of maintaining ecosystem balance, resulting in various disasters in various regions. On the other hand, the development of ecological intelligence in early childhood is only a formality and has not been fully maximized. In relation to this situation, this study aims to develop ecological intelligence through experiential learning as a preventive effort to build awareness of the importance of maintaining ecosystem balance and environmental concern. This type of research is qualitative with an observational approach. This approach was chosen to understand in depth the process of developing ecological intelligence in students through the application of experiential learning-based learning based on direct observation of behavior, attitudes, and interactions in natural learning. Data collection was conducted through participant observation, interviews, and supporting documentation. Data analysis was carried out descriptively and qualitatively through classification of observation data, data reduction, data presentation and drawing conclusions using the Miles and Huberman model. Data validity was carried out through time triangulation, namely through repeated observations, technical triangulation through observation and documentation, observation persistence, and audit trails through observation data records